2011
DOI: 10.1097/ta.0b013e3182151961
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Investigation of Long-Term Cognitive Impairment and Psychological Distress in Moderately Versus Severely Injured Trauma Intensive Care Unit Survivors Without Intracranial Hemorrhage

Abstract: Long-term cognitive impairment is highly prevalent in TICU survivors without intracranial hemorrhage as are psychologic difficulties. Injury severity, concussion status, and delirium duration were not risk factors for the development of neuropsychological deficits in this cohort. Individuals with moderately severe injuries seem to be as likely as their more severely injured counterparts to experience marked cognitive impairment and psychologic difficulties; thus, screening efforts should focus on this potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
(32 reference statements)
0
28
0
2
Order By: Relevance
“…Among these patients, increasing duration of delirium during acute critical illness in the ICU was an independent predictor of worse cognitive performance at follow-up, after adjustment for age, education, preexisting cognitive function, severe sepsis, and exposure to sedatives in the ICU (8). Similar cognitive testing of 108 1-year survivors of acute critical illness after trauma (without intracranial hemorrhage) showed impairments in about one-half of the subjects, although nearly one-half of the study cohort had returned to either fulltime or part-time work at the time of assessment (20). These studies and others indicate that patients returning to the ORIGINAL RESEARCH community after treatment for acute critical illness often experience subclinical cognitive impairment and that the duration of delirium in the ICU is among factors influencing the risk of this long-term outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Among these patients, increasing duration of delirium during acute critical illness in the ICU was an independent predictor of worse cognitive performance at follow-up, after adjustment for age, education, preexisting cognitive function, severe sepsis, and exposure to sedatives in the ICU (8). Similar cognitive testing of 108 1-year survivors of acute critical illness after trauma (without intracranial hemorrhage) showed impairments in about one-half of the subjects, although nearly one-half of the study cohort had returned to either fulltime or part-time work at the time of assessment (20). These studies and others indicate that patients returning to the ORIGINAL RESEARCH community after treatment for acute critical illness often experience subclinical cognitive impairment and that the duration of delirium in the ICU is among factors influencing the risk of this long-term outcome.…”
Section: Discussionmentioning
confidence: 88%
“…To our knowledge, no study has attempted to determine if a mental health disorder is a prognostic factor in patients undergoing surgery for femoroacetabular impingement or for any orthopaedic issue in an active-duty population. The trauma, spine, arthroplasty, and hand literature have shown poor outcomes in civilian patients with mental health diagnoses such as PTSD, depression, and anxiety [11][12][13][14] . This raises the question as to whether an interventional program to improve mental health might be beneficial prior to treating patients surgically for femoroacetabular impingement or other musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hoge et al reported that up to 29% of service members screened positive for posttraumatic stress disorder (PTSD), anxiety, or depression after deployment to Iraq 10 . Studies in the trauma, spine, and hand literature have also shown poor outcomes in civilian patients with mental health diagnoses [11][12][13] . Variable outcomes have been reported for arthroplasty 14,15 .…”
mentioning
confidence: 99%
“…Čimbenici rizika za nastanak psihijatrijske bolesti [npr, tjeskoba, depresija, posttraumatski stresni poremećaj] slični su onima za kognitivne [10,11,12]. Za nastanak sindroma rizik povećavaju postojeća anksioznost i depresija, kao i ženski spol, starosna dob <50 godina, niži stupanj obrazovanja, već postojeća invalidnost/nezaposlenost, uživanje alkohola, primjena sedativa i analgezije [13].…”
Section: Psihički čImbeniciunclassified